Computers in Law and Society: Introduction - Robert P. Bigelow (Washington University Law Quarterly, 1977)
The following introduction by Robert Bigelow highlights several issues which have developed during the first quarter-century of the computer age, and which are discussed more fully in the remaining pages of this Symposium.